Expectations do not need to be accurate to be maintained: Valence and need for cognitive closure predict expectation update vs. persistence - Henss, Larissa; Pinquart, Martin (Frontiers in Psychology, 2023)
Expectations about us and our environment serve to successfully anticipate the future, make accurate predictions, and guide behaviour and decisions. However, when expectations are not accurate, individuals need to resolve or minimize incongruence. Coping is especially important when expectations affect important domains such as students’ academic self-concept. Whether expectations are adjusted after expectation violation (accommodation), maintained by denying the discrepancy (immunization), or whether individuals modify behaviour to minimize the likelihood of future expectation violations (assimilation) depends on situational and dispositional predictors. In our experiment, we examined valence of expectation violation (positive vs. negative) as a situational predictor together with need for cognitive closure (NCC) as a dispositional predictor with N = 297 participants in a word riddle study. MANCOVA revealed that students tended to assimilate and accommodate more strongly after worse-than-expected achievement, and also NCC promoted both stronger accommodation and assimilation. NCC interacted with the valence of expectation violation: individuals with high NCC reported more assimilation and accommodation only after worse-than-expected achievement. The results replicate and extend previous findings: individuals do not always strive to have the most accurate expectations possible. Instead, both affective (valence) and cognitive (NCC) predictors appear to affect which coping strategy is preferred by the individual.